Advances in glucose monitoring: Improving diabetes management through evidence-based medicine. Issue 5 (October 2020) - Mazze, Roger
Highlights: Evidence-based decision-making requires unbiased data. Continuous glucose monitoring will replace biased self-monitored blood glucose. Continuous glucose monitoring measures diurnal patterns under routine conditions. Ambulatory glucose profile characterizes exposure, variability, and stability. Significant glucose improvement occurs using continuous glucose monitoring. Abstract: After 50 years SMBG use remains equivocal. CGM, may face the same fate. While it has been reported that CGM use results in improved HbA1c, the margin is small, and the studies scant. Like SMBG, CGM was introduced as "here's something new, try it." For CGM's potential to be fully realized it must be understood that it can discover underlying metabolic perturbations that would otherwise go undetected; it can measure the frequency, duration, magnitude and distribution of glucose exposure, variability and stability under conditions of daily living which in turn lead to more precise therapies, resulting in improved outcomes.